Metabolism and detoxification of pesticides in plants - Zhang, Jing Jing; Yang, Hong (The Science of the total environment, 2021)
Pesticides make indispensable contributions to agricultural productivity. However, the residues after their excessive use may be harmful to crop production, food safety and human health. Although the ability of plants (especially crops) to accumulate and metabolize pesticides has been intensively investigated, data describing the chemical and metabolic processes in plants are limited. Understanding how pesticides are metabolized is a key step toward developing cleaner crops with minimal pesticides in crops, creating new green pesticides (or safeners), and building up the engineered plants for environmental remediation. In this review, we describe the recently discovered mechanistic insights into pesticide metabolic pathways, and development of improved plant genotypes that break down pesticides more effectively. We highlight the identification of biological features and functions of major pesticide–metabolized enzymes such as laccases, glycosyltransferases, methyltransferases and ATP binding cassette (ABC) transporters, and discuss their chemical reactions involved in diverse pathways including the formation of pesticide S–conjugates. The recent findings for some signal molecules (phytohomormes) like salicylic acid, jasmonic acid and brassinosteroids involved in metabolism and detoxification of pesticides are summarized. In particular, the emerging research on the epigenetic mechanisms such DNA methylation and histone modification for pesticide metabolism is emphasized. The review would broaden our understanding of the regulatory networks of the pesticide metabolic pathways in higher plants. [Display omitted] •Plants can metabolize pesticides through degradative enzymes and sequestration.•There are diverse reactions by which pesticides are metabolized.•Some signal molecules are involved in pesticide metabolism and detoxification.•Epigenetic mechanism is involved in metabolism of pesticides in plants.